(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article is devoted to the level of euphemisms and dysphemism in expressing condolences in English and Uzbek languages. The article reveals a cross-cultural comparison of these linguistic phenomena when expressing condolences in English and Uzbek and their impact on language, culture and social norms. The degree of euphemisms and dysphemism in condolence speech was analyzed from cross-cultural comparison in three novels that were selected from English literature “Testament of Youth” by Vera Britain and from Uzbek “Ikki eshik orasi” by Utkir Hoshimov and “Shaytanat” by Tohir Malik. Furthermore, cross-cultural analysis was conducted to explore how these linguistic dynamics are displayed and interpreted across different cultural and linguistic frameworks, providing significant viewpoints into their diverse role in forming communicative practices and social conventions. Having conducted the research, the following findings were revealed: (1) the Uzbek language employs a greater number of euphemisms when conveying condolences compared to the English. (2) using of dysphemism in the context of expressing condolence was not found to be prevalent in English. However, it was noted that dysphemism presence or absence may depend on the attitude and language choices of the condolence giver. The practical implications of this study can be used to understand cultural differences in expressing condolences and enrich cross-cultural communication.